2017
DOI: 10.3390/w9010013
|View full text |Cite
|
Sign up to set email alerts
|

Fish Welfare in Aquaponic Systems: Its Relation to Water Quality with an Emphasis on Feed and Faeces—A Review

Abstract: Abstract:Aquaponics is the combination of aquaculture (fish) and hydroponic cultivation of plants. This review examines fish welfare in relation to rearing water quality, fish feed and fish waste and faeces to develop a sustainable aquaponic system where the co-cultured organisms, fish, bacteria in biofilters and plants, should be considered holistically in all aquaponics operations. Water quality parameters are the primary environmental consideration for optimizing aquaponic production and for directly impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 90 publications
1
89
0
Order By: Relevance
“…The absence of roots leads most likely to the murky water conditions in the control system as shown by measurements of the water turbidity (Table 2). Other effects, such as the release of substances from the roots into the process water, were not a matter of this study, but cannot be excluded [10]. As discussed in Section 4.1, the plants inside the hydroponic units helped to maintain system stability, reducing water replacement due to their nutrient uptake.…”
Section: Plant Productionmentioning
confidence: 96%
See 1 more Smart Citation
“…The absence of roots leads most likely to the murky water conditions in the control system as shown by measurements of the water turbidity (Table 2). Other effects, such as the release of substances from the roots into the process water, were not a matter of this study, but cannot be excluded [10]. As discussed in Section 4.1, the plants inside the hydroponic units helped to maintain system stability, reducing water replacement due to their nutrient uptake.…”
Section: Plant Productionmentioning
confidence: 96%
“…They grow quickly have an effective feed conversion ratio (FCR). However, it remains uncertain to what extent the aquaponic environment influences the wellbeing of this fish species [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fact that discharging aquacultural waste might cause eutrophication, valuable nutrients are simply wasted. P is mainly lost through faeces in fish production (Neto and Ostrensky, 2013;Yavuzcan Yildiz et al, 2017). Håkanson et al (1998) even reported that 70% of the P fed to fish is lost through faeces.…”
Section: Recirculating Aquaculture Systems (Ras)mentioning
confidence: 99%
“…However, this type of model can demonstrate to what degree the implementation of a third loop, in addition to the RAS and hydroponic loops, can impact the required scale of hydroponic cultivation area. For these calculations, it was assumed that 55% of the nutrient input (via fish feed) ends up in sludge (Neto and Ostrensky, 2013;Yavuzcan Yildiz et al, 2017), and that the remineralization potential of an upflow anaerobic sludge blanket (UASB) reactor is approximately 90% (Mirzoyan and Gross, 2013).…”
Section: Recirculating Aquaculture Systemmentioning
confidence: 99%
“…The wastewater treatment also allows solids to be removed or reintroduced back into the system as dissolved solids (Hijran Yavuzcan Yildiz, 2017) that supply plants additional nutrients. The fish species to be grown have limitations on the amount of (Zealand, 2000)Total Dissolved Solids and other water quality requirements that must be met if the produce is to be resold.…”
Section: Aquaponics Subsystemsmentioning
confidence: 99%